Investigations on the microstructure and mechanical property of friction stir processed AA6061 aluminium sheet metal reinforced with Al2O3 surface composite. (1st January 2014) - Prakash, T.; Sasikumar, P.; Sivasankaran, S.
Friction stir processing (FSP) is an emerging surface engineering technology that can eliminate casting defects locally by refining microstructures, thereby, improving the mechanical properties of the material. In this study, the influence of the FSP on the microstructure and mechanical properties in terms of hardness for commercially available AA6061 Al sheet metals reinforced with aluminium oxide was studied and investigated. Samples were subjected to FSP by varying the rotational and traverse speed. From the microstructural evaluation, it was observed that the grain size of the processed area was around 70% decreased as compared to unprocessed parent metal. The hardness results showed that the strength of stirred surface area was around 1.75 times higher than the unstirred surface area. Further wear test showed that the wear resistance were increased with respect to increase in rotational and traverse speed.